Association of Early Preterm Birth with Abnormal Levels of Routinely Collected First and Second Trimester Biomarkers - Jelliffe-Pawlowski, Laura L. (2013)
OBJECTIVE: To examine the relationship between typically measured prenatal screening biomarkers and early preterm birth in euploid pregnancies. STUDY DESIGN: Included were 345 early preterm cases (< 30 weeks) and 1,725 controls drawn from a population-based sample of California pregnancies that all had both first and second trimester screening results. Logistic regression analyses were used to compare patterns of biomarkers in cases and controls and to develop predictive models. Replicability of the biomarker-early preterm relationships revealed by the models was evaluated by examining the frequency and associated adjusted relative risks (RRs(adj)) for early preterm birth and for preterm birth in general (< 37 weeks) in pregnancies with identified abnormal markers compared to those without these markers in a subsequent independent California cohort of screened pregnancies (n = 76,588). RESULTS: The final model for early preterm birth included first trimester pregnancy-associated plasma protein A (PAPP-A) ≤ the 5(th) percentile, second trimester alpha-fetoprotein (AFP) ≥ the 95(th) percentile, and second trimester inhibin (INH) ≥ the 95(th) percentile (odds ratios 2.3 to 3.6). In general, pregnancies in the subsequent cohort with a biomarker pattern found to be associated with early preterm delivery in the first sample were at an increased risk for early preterm birth and preterm birth in general (< 37 weeks) (RRs(adj) 1.6 to 27.4). Pregnancies with two or more biomarker abnormalities were at particularly increased risk (RRs(adj) 3.6 to 27.4). CONCLUSION: When considered across cohorts and in combination, abnormalities in routinely collected biomarkers reveal predictable risks for early preterm birth.